The Malaysian Perception Toward Foreign Tourists in Malaysia - Alvarez, Ravis Chena; Atikah, Siti Nor (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
ABSTRACT The purpose of the study was to collect, process, analyze and describe the perception of Malaysian towards foreign tourists in Malaysia. This research is a descriptive analysis. Data collected using observation, interview, and documentation techniques. Data analysis in the study was carried out using data reduction techniques, data interpretation and conclusion drawing. The results show that 1). Public perception of foreign tourists in Malaysia shows that Malaysians are very supportive of foreign tourists coming to Malaysia. 2). Positive and negative impacts of foreign tourists coming to Malaysia; the positive impact, with the presence of tourists can increase Malaysia's foreign exchange and advance the country. As for the negative impact, Malaysians also negatively perceive black tourists such as from Bangladesh, Sri Lanka who usually bring problems in Malaysia such as narcotics and crime.